Benign Neonatal Hemangiomatosis. (29th October 2022) - Miller, Austinn C.; Gordon, Elliott S.; Peterson, Christy R.; Cohen, David J.; Bowe, Andrew C.
Abstract : Background: Benign neonatal hemangiomatosis (BNH) is a rare, self-limiting subtype of infantile hemangiomas (IHs), in which infants with multiple cutaneous hemangiomas lack visceral involvement. Other subtypes of IHs exist that may mimic BNH and can be life-threatening depending on hemangioma location and size. Clinical Findings: At birth, a 29 5 /7 -week preterm female presented with several pinhead-sized pink papules distributed throughout her body. At 10 days of age, the patient had 12 enlarged domed-shaped red papules in a generalized distribution throughout her body. Over several weeks, the number and size of the domed-shaped red papules continued to increase to a total of 26 located on the head, chest, abdomen, back, legs and arms. They were of firm consistency with both smooth and lobulated surfaces. Primary Diagnosis: A diagnosis of BNH was made after extensive workup did not reveal any extracutaneous hemangiomas. Interventions: Due to the lack of extracutaneous involvement and low-risk location/size of hemangiomas in our patient, no interventions were pursued and an observation-only approach was implemented. Outcomes: The patient remained stable while followed up over 8 months, with the size of the hemangiomas only increasing slightly in proportion to the patient's natural body growth. Practice Recommendations: Given the life-threatening nature of certain hemangioma subtypes, it is important to implement a proper workup and subtype diagnosis as early as possible in any infant with multiple hemangiomas.